Individual, Work, and Financial Factors on Job Satisfaction and Remaining as a Midwife - Restu Widyayu; Oskar Renagalih Amarta; Ratna Dwi Wulandari; Stefanus Supriyanto; Djazuli Chalidyanto; Nur Anisah Rahmawati; Raisa Manika Purwaningtias (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The delivery of health services at mother and child hospitals involves the midwife's role. Midwives are more responsible for providing patient care when faced with high Bed Occupation Rate (BOR) situations and emergency cases. However, several factors can affect midwives' turnover rates in hospitals. Purpose: This study aimed to analyze the relationship between individual factors (age, marital status, education level, years of service, and employment status), work factors (workload, work environment, and work stress), and financial compensation on job satisfaction and intention to leave midwives as well as recommendations for reducing turnover rates. Methods: This study was conducted at the Trisna Medika Women and Children Hospital, Tulungagung, Indonesia, in April 2022. The questionnaires were distributed to 65 respondents. The research results were analyzed using the partial least squares (PLS)Structural Equation Model (SEM) method. Results: Individual factors had no significant effect on job satisfaction or intention to leave. The variables that directly affect the intention to leave (medium) are workload, financial compensation (strong), and job satisfaction (medium). Job satisfaction is directly affected (moderately) by financial compensation and work stress. The indirect effect shows a significant relationship between job stress and job satisfaction in the work environment. Conclusion: The direct effect of financial compensation on intention to leave was stronger than the effect of financial compensation on job satisfaction.